Daily Use of Social Media Is Associated with More Body Dissatisfaction of Teenage Girls in a Large Cross-Cultural Survey - Clotilde Napp; Thomas Breda (Institute of Labor Economics (IZA), 2022)
Most teenagers spend several hours per day on social media. We provide a large-scale investigation of the relationship between social media daily usage and body dissatisfaction among a sample of more than 50,000 15 y.o. students. This relation is positive and large for girls—higher use of social networks is associated with higher dissatisfaction about their body—and negative for boys. The positive relation for girls is observed in all eight countries included in the study, covering very different cultural contexts (e.g., Georgia, Ireland, Spain, Mexico, Panama or Hong Kong). It is observed for all girls, no matter their body mass index (BMI), their academic performance, and their socioeconomic background. Instrumenting social networks consumption by students' or students' peers' internet access at home while controlling finely for other students' or students' peers' household characteristics suggests that the relationship between social media consumption and girls' body dissatisfaction could be causal.
Keywords: I12; L82; 330; social media; body dissatisfaction